Russia - European Union: the Impact of the Restrictive Measures on the Development of Bilateral Relations - Yuliya V. Puzyreva (Московский журнал международного права)
The article analyzes the current state of relations between the European Union and Russia, with a focus on the study of the causes, nature and consequences of the “freezing” bilateral co-operation, accompanied by the introduction of the European Union in respect of the Russian Federation set of restrictive measures and the application of the latest responses to protect their interests.